Peran Media Sosial Untuk Meningkatkan Jumlah Hunian Penginapan Batara White House Di Kapala Pitu Kabupaten Toraja Utara - Merlin Merlin; Abedneigo Carter Rambulangi (Universitas Kristen Indonesia Toraja, 2023)
This research aims to determine the role of social media in increasing the number of residences at the Batara White House accommodation in Kapala Pitu, North Toraja Regency. This type of research is qualitative. The informants in this research were the manager and 2 residential people at the Batara White House. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The results obtained are that in increasing the number of residences at Batara White House, the management uses the role of social media Instagram. In using social media Instagram, the management of Batara White House makes aesthetic posts with interesting captions. With the role of social media, starting from the beginning of March until May 2023, the number of residences has increased, namely in March there were 693 residences, in April there were 867 residences, and in May there were 889 residences. This happens because there is consistency in uploading Instagram stories and also diligently reposting posts from other users who come to visit.